THE ROLE OF MICROBIAL ENGRAFTMENT AND KEYSTONE SPECIES IN THE EFFICACY OF FAECAL MICROBIOTA TRANSPLANTATION IN PATIENTS WITH INFLAMMATORY BOWEL DISEASE - A REVIEW OF RECENT STUDIES - Kowalska, Monika; Zięba, Anita; Domin, Michał; Całka, Justyna; Ścibisz, Katarzyna; Ollik, Karolina; Harenza, Kamil; Taranowicz, Mateusz; Kowalczyk, Olga; Zdobylak, Dominika (International Journal of Innovative Technologies in Social Science, 2026)
Background: Inflammatory bowel diseases, including Crohn’s disease and ulcerative colitis, are chronic relapsing disorders in which alterations of the gut microbiota contribute to disease pathogenesis. Despite advances in pharmacological therapies, sustained remission remains difficult to achieve in many patients, prompting interest in microbiome-targeted interventions such as faecal microbiota transplantation.Objectives: This study aimed to review evidence published between 2015 and 2025 on the efficacy of faecal microbiota transplantation in inflammatory bowel diseases, with emphasis on donor microbiota engraftment, keystone taxa, the donor effect, and differences between ulcerative colitis and Crohn’s disease.Methods: A narrative–systematic review of clinical, metagenomic, and ecological studies addressing faecal microbiota transplantation in inflammatory bowel diseases was conducted using major biomedical databases.Results: Clinical response following faecal microbiota transplantation was more consistently associated with stable and functional engraftment of donor-derived microbial strains than with restoration of microbial diversity alone. Evidence supporting this association was stronger in ulcerative colitis, whereas data in Crohn’s disease remained limited and largely observational. Variability in outcomes appeared to reflect interactions between donor and recipient microbiota.Conclusions: Faecal microbiota transplantation represents a complex ecological intervention, the efficacy of which depends on engraftment stability, functional reconstruction of the gut microbiome, and recipient-specific ecological context.